A single-atom dispersed zirconium-silicon modified alumina carrier and its preparation method and application
By dispersing zirconium silicon in a single atomic state in the catalyst support, the problem of poor stability of the existing catalyst support at high temperatures is solved, and the effect of maintaining a high specific surface area and strength at high temperatures is achieved.
Patent Information
- Application Number
- CN202211612703.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The existing catalyst support materials have poor stability at high temperatures, resulting in a decrease in catalyst activity, limiting the application of new green propellants.
The single-atom dispersed zirconium silicon modified alumina support was prepared by the sol-gel method. The zirconium element and the silicon element were distributed in the alumina grain surface and bulk phase in the isolated single atomic state, enhancing the high temperature stability of the support.
A catalyst support with high specific surface area and strength above 1200°C was achieved, which solved the problem of structural rearrangement and transformation of the catalyst at high temperatures, and improved the stability of the single-component thrust catalyst.
Smart Images

Figure CN116212844B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst carrier preparation, and particularly relates to a single-atom dispersed zirconium-silicon modified alumina carrier and a preparation method and application thereof. Background Art
[0002] Monopropellant thrusters are widely used in attitude and orbit control systems of aerospace vehicles such as satellites, launch vehicles, spacecraft, and space stations. They play a decisive role in the precise orbit insertion, orbit maintenance, attitude control, and rendezvous and docking of various aerospace vehicles. Their development level is one of the important indicators of a country's aerospace technology. Hydrazine catalytic decomposition technology is currently the most commonly used monopropellant propulsion technology. Ir / Al 2 O 3 The catalyst is currently the most commonly used hydrazine decomposition catalyst. This technology was developed in the 1960s. Now, as people gradually increase their requirements for the service life of various types of spacecraft, Ir / Al 2 O 3 Catalyst stability is the bottleneck restricting the further development of this technology. Studies have found that the influence of Ir / Al 2 O 3 An important factor in catalyst stability is that the alumina material used as a catalyst carrier gradually crystallizes during long-term high-temperature use, which leads to the volume shrinkage of the catalyst and the aggregation of active components, resulting in a decrease in catalyst activity. Compared with hydrazine propulsion technology, new green propellants represented by ADN (ammonium dinitramide) and HAN (hydroxylamine nitrate) have the advantages of being non-toxic, environmentally friendly, high specific impulse, and chlorine-free. They are a new generation of high-performance propellants, but the catalytic decomposition temperature of this type of propellant is higher than that of hydrazine. For example, the adiabatic decomposition temperature of ADN is as high as 1400°C, which is much higher than the catalytic decomposition temperature of hydrazine (about 900°C), which requires the catalyst to work at extremely high temperatures. How to solve the problem of high-temperature stability of catalyst carrier materials is a bottleneck problem for the practical application of green propulsion technology. A large number of studies have shown that alumina is one of the most suitable carrier materials for various monocomponent thruster catalysts. Therefore, the development of high-temperature resistant alumina carrier preparation technology has become an urgent problem that needs to be solved in the development of various monocomponent propulsion technologies.
[0003] Studies have shown that the introduction of alkali metals, alkaline earth metals, rare earth elements, silicon, phosphorus and other modified elements into alumina can improve the high temperature stability of alumina. Commonly used alumina modification methods include kneading extrusion method, vapor deposition method, impregnation method, coprecipitation method, sol-gel method, microemulsion method, cellulose template method, etc.
[0004] Patent CN102039148A discloses a method for preparing silicon- and phosphorus-modified activated alumina by extrusion. The main steps are: adding silicon- and phosphorus-containing compound solutions to pseudo-boehmite, extruding on an extruder, and drying and calcining to obtain silicon- or phosphorus-containing γ-Al 2 O 3 The modified alumina prepared by this method can only be distributed on the outer surface of the alumina grains, and cannot enter the interior of the grains. This method can only be used to adjust the surface acidity and macroscopic pore structure of the alumina carrier, and has limited effect on the high-temperature stability of the alumina carrier. Patent CN102491389A uses an impregnation method to load the modified elements on pseudo-boehmite, and after calcination at 1000°C, alumina modified with alkaline earth elements and rare earth elements is obtained, with a specific surface area of 93m 2 / g. In this type of modified alumina prepared by impregnation, the modified elements are distributed on the inner and outer surfaces of the alumina in the form of multi-atom aggregates such as grains or clusters, which makes it difficult to penetrate into the bulk phase, resulting in poor modification effect. When the temperature difference exceeds 1000°C, the specific surface area decreases significantly. Patent CN109772289A discloses an improved impregnation method, firstly, the pre-prepared γ-Al 2 O 3 Disperse it into a mixture of polyethylene glycol and water to avoid alumina agglomeration and caking, then add lanthanum nitrate solution to make lanthanum nitrate evenly adsorbed on the surface of alumina. Compared with the preparation of lanthanum modified alumina by ordinary impregnation method, after calcination at 1100℃, the specific surface area increases from 79m 2 / g, increased to 156m 2 / g. These disclosed preparation methods show that the high temperature stability of modified alumina can be greatly improved by increasing the dispersion of the modifying elements. However, the heat-resistant temperature of the modified alumina prepared by these methods generally does not exceed 1100°C because the modifying elements are only distributed on the outer surface of the alumina grains.
[0005] Patent CN102701246A discloses a method for further distributing the modified element inside the alumina grains. The method uses lanthanum nitrate and aluminum sol coprecipitation to prepare rare earth La-modified alumina. After calcination at 1100°C, the specific surface area is 63m 2 / g. The main problem of this method is that due to the different pH values of the deposition of lanthanum ions and aluminum ions in the solution, the two cannot be deposited at the same time. Therefore, the distribution of lanthanum in the sediment is not uniform. After being converted into alumina, if the roasting temperature is greater than 1100°C, the alumina will be trans-crystal sintered and the specific surface area will drop sharply.
[0006] In order to improve the dispersion of the modified elements inside the alumina grains, people have studied a series of methods to improve the dispersion of the modified elements by reducing the size of the alumina particles. Typical methods include sol-gel method, reverse microemulsion method and cellulose template method. Patent CN1562753A combines sol-gel and supercritical drying technology, and discloses a process for preparing alumina wet gel by sol-gel method and alumina dry gel by supercritical fluid drying method using sodium metaaluminate and water glass as raw materials. The prepared high-temperature resistant alumina has a small particle size. After being treated in an air atmosphere at 1100℃ for 4 hours, its specific surface area is as high as 165m 2 Patent CN1250455C discloses a method for preparing high-temperature high-surface-area aluminum oxide and aluminum-containing composite oxide by reverse microemulsion method, wherein aluminum and soluble inorganic salts of modifying elements are prepared into reverse microemulsion, which is mixed with reverse microemulsion containing alkaline substances to prepare sol, and aluminum oxide and aluminum-containing composite oxide materials with high thermal stability can be obtained after filtering, drying, roasting and other treatments. The Si-modified aluminum oxide prepared by this method has a specific surface area of 185.2 m after being roasted at 1100°C for 10 hours. 2 / g. The product synthesized in a tiny reactor such as a reverse microemulsion has a very small particle size, so the modified element obtains a better dispersion. Therefore, compared with other methods, the specific surface area at high temperature is greatly improved. The cellulose template method originates from the idea of using a porous polymer mold as a template. The cellulose material used as a template should have a nanoporous structure and capillary channels. The operation process is to first dissolve the precursor, and then dry and calcine it after adsorption by the template to obtain the product. The literature (Applied catalysis A: General, 2001, 210: 287-300) reported that La-modified alumina prepared with filter paper as a template had a specific surface area of 141m after calcination at 1050°C. 2 / g. The cellulose template method achieves relatively uniform dispersion of the modified elements by controlling the particle size.
[0007] These published methods show that the high temperature stability of alumina can be greatly improved by increasing the dispersion of the modified elements on the surface and bulk of alumina grains. However, in the preparation of these modified alumina, the modified elements are mostly distributed on the surface and bulk of the modified alumina grains in the form of tiny grains or nanoclusters, and their ultimate temperature resistance is about 1100°C. If the temperature exceeds 1200°C and reaches or approaches the crystal transformation temperature of alumina, the alumina will sinter quickly and the specific surface area will drop sharply.
[0008] Theoretically, the limit of the dispersion of modified elements is to disperse them in the carrier in a single atomic state. In 2011, the team of Academician Zhang Tao found that when the metal reaches a single atomic state in the carrier, it will cause significant changes in the surface free energy, quantum size effect, unsaturated coordination environment, and strong metal-carrier interaction of the element, resulting in performance significantly different from the nano and sub-nanometer dispersion state. Patent CN103342537A deposits hexamethyldisilazane vapor in alumina bulk aerogel to prepare a high-temperature resistant alumina aerogel material. After high-temperature treatment at 1200°C, the linear shrinkage is only 5%, and the specific surface area is as high as 280m 2 / g. The reason why it can maintain such a high specific surface area at 1200℃ is that Si is dispersed in a single-atom state on the surface of alumina nanoparticles, the solid phase component of aerogel, which improves the high-temperature stability of alumina nanoparticles. However, since aerosols, also known as "solid smoke", have extremely low density, they must be compressed into particles with a macroscopic shape when used as catalyst carrier materials, because Si can only be vapor-deposited on the outer surface of alumina particles and cannot enter the bulk phase. After compression molding, the high-temperature resistance drops sharply, so it cannot be used as a catalyst carrier material, especially for the preparation of single-component thruster catalyst carrier materials that require both high strength and specific surface area. In addition, the vapor deposition method has a complex process, harsh conditions, and high production costs. Summary of the invention
[0009] In view of the above problems, the present invention provides a single-atom dispersed zirconium-silicon modified alumina carrier and its preparation method and application. Under the action of a complexing agent, the modified element can be distributed in a single-atom state simultaneously on the surface and bulk of alumina crystals prepared by a sol-gel method. The method is simple in process, low in production cost, and easy to scale up industrially. The zirconium element and silicon element in the carrier of the present invention are dispersed in the alumina in an isolated single-atom state. Under the action of single-atom effects such as coordination unsaturation effect, quantum size effect, and strong metal-carrier interaction, the carrier of the present invention has good high-temperature stability, which solves the high-temperature stability problem of single-component thruster catalysts.
[0010] In order to achieve the above object, the technical solution of the present invention is as follows:
[0011] On the one hand, the present invention provides a monatomic dispersed zirconium-silicon modified alumina carrier, which is composed of zirconium oxide, silicon oxide and alumina; by weight, the zirconium oxide content is 0.5-10%, the silicon oxide content is 0.5-8%, and the balance is alumina; the zirconium element and the silicon element are distributed in the isolated monatomic state simultaneously on the surface and bulk of the alumina grains.
[0012] In the above technical solution, further, the catalyst support material is composed of zirconium oxide, silicon oxide and aluminum oxide, and the zirconium oxide content is 5-8% by weight, the silicon oxide content is 5-8% by weight, and the balance is aluminum oxide.
[0013] In the above technical solution, further, the specific surface area of the catalyst support material is ≥180m 2 / g, pore volume ≥ 0.25cm 3 / g, strength 36~70Mpa.
[0014] Another aspect of the present invention provides a method for preparing the above-mentioned monoatomic dispersed zirconium-silicon modified alumina carrier, the method comprising the following steps:
[0015] (1) Preparing a precursor solution: dissolving sodium aluminate in water to prepare an aluminum-containing precursor solution, dissolving a soluble zirconium salt in water, adding a complexing agent I, preparing a zirconium-containing precursor solution, dissolving sodium silicate in water, adding a complexing agent II, preparing a silicon-containing precursor solution;
[0016] (2) preparing aluminum-based composite powder: taking the same volume of aluminum-, zirconium-, silicon-containing precursor solution and dilute acid solution obtained in step (1), adding the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution to the aluminum-containing precursor solution at the same flow rate, controlling the stirring speed to 1800-3600 rpm, and the reaction temperature to 80-100° C. to obtain aluminum-based sol, and after standing for 10-24 hours, adjusting the pH value of the system to 5-9 with a dilute acid solution to obtain aluminum-based gel, and then washing, filtering, drying, and crushing to obtain aluminum-based composite powder;
[0017] (3) Powder molding: The aluminum-based composite powder obtained in step (2) is mixed with a binder and a molding aid, kneaded, molded, granulated, and then calcined to obtain a catalyst carrier material with a macroscopic shape.
[0018] In the above technical solution, further, in step (1), the soluble zirconium salt is one or more of zirconium tetrachloride, zirconium oxychloride, zirconium sulfate, zirconium oxysulfate, and zirconium isopropoxide;
[0019] The complexing agent I is one or more of 1,10-o-phenanthroline, disodium ethylenediaminetetraacetate, thioglycolic acid, mercaptoethylamine, sodium dimercaptopropanesulfonate, thiourea, 8-hydroxyquinoline, potassium cyanide, citric acid, tartaric acid, oxalic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid, ethylenediaminetetrapropionic acid, and triethylenetetramine;
[0020] The complexing agent II is one or more of catechol, ammonium fluoride, acetylacetone, triethanolamine, and sulfosalicylic acid;
[0021] The dilute acid solution is any one of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid and acetic acid, and the equivalent concentration of the dilute acid solution is 2-5 mol / L.
[0022] In the above technical solution, further, in step (2), the parallel flow rate is 1 to 5 ml / s;
[0023] In the same volume of the zirconium-containing precursor solution, the silicon-containing precursor solution, the dilute acid solution, and the aluminum-containing precursor solution, the molar ratio of zirconium, silicon, hydrogen ions, and aluminum is (2-33): (4-85): 1000: 1000;
[0024] The drying temperature is 100-120° C., and the drying time is 6-15 hours.
[0025] In the above technical solution, further, in step (3), the calcination temperature is 1100-1300°C;
[0026] The mass ratio of the aluminum-based composite powder, the binder and the molding aid is 100:(53-58):(1-3).
[0027] In the above technical solution, further, in step (3), the macroscopic catalyst carrier material is a particle with a circular, elliptical or multi-petal cross-section, and a screening diameter of 0.5 to 5 mm, preferably 0.8 to 2.0 mm.
[0028] In another aspect, the present invention provides an application of the above-mentioned monatomic dispersed zirconium-silicon modified alumina carrier in the propellant decomposition reaction of a monocomponent thruster.
[0029] The beneficial effects of the present invention are:
[0030] 1. In the modified alumina carrier prepared by the preparation method of the present invention, the modified element is distributed in the carrier in an isolated single-atom state. Due to the coordination unsaturation effect, on the one hand, the single-atom distributed modified element can produce a strong interaction with alumina, and the compound of the modified element is firmly locked in the γ-Al in an interface bonding manner. 2 O 3 On the other hand, the coordination unsaturation effect can drive the modified elements distributed in the form of isolated single atoms to be inserted into the spinel structure with cation defects, occupying the gaps formed by oxygen ions in the dense packing, thereby reducing the Al 2 O 3 The ion activity in the lattice suppresses the Al 3+ and O 2- The single-atom dispersed zirconium-silicon modified alumina carrier of the present invention has good high-temperature stability under the action of single-atom effects such as coordination unsaturation effect, quantum size effect, and strong metal-carrier interaction.
[0031] 2. The present invention uses zirconium as a modifying element. Zirconium oxide itself is currently one of the most advanced refractory materials in the world. It has a high melting point, is non-oxidizing and other excellent high-temperature properties. It can be used for a long time in an ultra-high temperature oxidizing atmosphere above 1500°C. The maximum operating temperature is as high as 2200°C, or even 2500°C. In the carrier of the present invention, zirconium in the form of isolated single atoms is firmly locked in the γ-Al in the form of ZrOAl. 2 O 3 At the grain corners, this ZrOAl bond also has good high-temperature stability, which can effectively solve the problem of easy sintering and agglomeration of elements with single atomic distribution, thereby preventing the structural rearrangement and crystal transformation process of alumina at higher temperatures.
[0032] 3. The present invention uses Si as a modifying element because the atomic radius of Si (110 pm) is similar to that of Al (143 pm) and slightly smaller than that of Al. Compared with other modifying elements, Si is more likely to enter the Al in the spinel structure. 3+ Ion vacancies suppress the Al 3+ and O 2- The fluidity of γ-Al 2 O 3 On the other hand, Si atoms can form Si-O-Al bonds with the surface of alumina grains, reduce the contact points between grains, increase steric hindrance, and thus prevent the sintering of grains.
[0033] 4. The present invention utilizes Si and Zr to modify simultaneously. Si and Zr occupy different positions of alumina grains, which can produce a synergistic effect and prevent the formation of γ-Al 2 O 3 Surface diffusion and structural rearrangement occur during phase transition.
[0034] 5. The present invention adopts the complexation sustained-release method and the sol-gel method to prepare the modified alumina distributed in a single-atom state. The preparation method is simple, the production cost is low, and it is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a high-resolution electron microscope photograph of sample 1 in Example 1, where a is 10 nm and b is 2 nm;
[0036] Figure 2 This is a high-resolution electron microscope photograph of sample 2 in Example 2;
[0037] Figure 3 This is a high-resolution electron microscope photograph of sample 4 in Example 4. DETAILED DESCRIPTION
[0038] The specific implementation modes of the present invention are further described in detail below in conjunction with the examples. The following examples are used to illustrate the present invention but are not used to limit the scope of the present invention.
[0039] Example 1
[0040] (1) Weigh 603 g of sodium aluminate (NaAlO 2 ) was dissolved in 800 ml of water, the solution was poured into a 1000 ml volumetric flask and fixed to the standard scale to prepare an aluminum-containing precursor solution; 49 g of zirconium oxychloride (ZrOCl 2 8H 2 O) was dissolved in 500 ml of water, and 110 g of 1,10-phenanthroline (C 12 H 8 N 2 ), after stirring and dissolving, transfer the solution to a 1000 ml volumetric flask and dilute to the standard mark with water to prepare a zirconium-containing precursor solution; weigh 38 g of sodium silicate (Na 2 SiO 3 ) was dissolved in 500 ml of water and 46 g of ammonium fluoride (FH 4 N), after stirring and dissolving, transfer the solution to a 1000ml volumetric flask and dilute to the standard mark with water to obtain a silicon-containing precursor solution; weigh 682g of concentrated nitric acid with a mass concentration of 68% and place it in a 1000ml volumetric flask, add water and shake well, and dilute to the standard mark to obtain a dilute nitric acid solution;
[0041] (2) 660 ml of the prepared zirconium-containing precursor solution, silicon-containing precursor solution and dilute acid solution were taken and placed in three 1000 ml dropping bottles with constant flow peristaltic pumps respectively; 660 ml of the prepared aluminum-containing precursor solution was taken and placed in a reactor with a jet flow agitator and a temperature control jacket; the temperature of the sodium aluminate solution was heated to 90° C. by the temperature control medium in the temperature control jacket; the stirring speed was set to 1800 rpm; the flow rate of each peristaltic pump was 3 ml / s; the constant flow peristaltic pump and the jet flow agitator were turned on at the same time; the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution were pumped into the reactor at the same flow rate and flow rate in parallel; and the mixture was cooled by the cooling device. The thermal integrated machine always controls the temperature of the reaction liquid in the reactor to 90°C. After the addition of liquid is completed, the peristaltic pump is turned off, and the stirring speed is maintained at 1800 rpm / min for 15 minutes to obtain an aluminum-based sol; after the obtained aluminum-based sol is allowed to stand in the reactor overnight, a dilute nitric acid solution is added dropwise to adjust the pH value of the system to 8 to obtain an aluminum-based gel; the obtained aluminum-based gel is transferred to a Buchner funnel, and repeatedly washed by suction filtration. When the PNa value of the filtrate is ≥3, the muddy wet gel after suction filtration is transferred to an oven and dried at 120°C for 6 hours to obtain a block dry gel, and the block dry gel is crushed into a powder with an average particle size of 10 μm by a jet mill;
[0042] (3) The water-powder ratio is controlled to be 0.53, and diluted nitric acid with a mass concentration of 4% is used as a binder, and sesbania powder is used as a molding aid. The amount of sesbania powder added is 2% of the mass of the powder. The prepared aluminum-based powder is kneaded into a plastic dough in a kneader; the dough is transferred to an extruder, and extruded into a cylindrical extrudate through a mold for preparing cylindrical extrudates. The diameter of the cylindrical extrudates prepared in this embodiment is 2 mm; the obtained extrudates are dried and prepared into cylindrical particles with an average length of 2 mm in a granulator, and then placed in a high-temperature furnace for calcination at a heating rate of 2°C / min, a constant temperature of 1200°C, a constant temperature time of 4 hours, and after natural cooling, zirconium and silicon modified aluminum-based composite catalyst carrier particles are obtained, which are recorded as sample 1.
[0043] The surface area and voidage analyzer ASAP 2420 manufactured by Micromeritics was used to analyze the 2 The specific surface area and pore volume of the obtained samples were measured by adsorption method, and the crushing strength of the obtained samples was measured by DLⅡ particle strength tester manufactured by Dalian Penghui Technology Development Co., Ltd. The test results are shown in Table 1.
[0044] Example 2
[0045] (1) Weigh 603 g of sodium aluminate (NaAlO 2 ) was dissolved in 800 ml of water, and the solution was poured into a 1000 ml volumetric flask and fixed to the standard scale to prepare an aluminum-containing precursor solution; first, 51 g of disodium ethylenediaminetetraacetate was weighed and dissolved in 1000 ml of water, and then 4 g of zirconium tetrachloride (ZrCl 4 ), stir and dissolve to obtain a zirconium-containing precursor solution; weigh 4g sodium silicate (Na 2 SiO 3 ) was dissolved in 1000 ml of water, and 10 g of catechol (C 6 H 6 O 2 ) stirring and dissolving to obtain a silicon-containing precursor solution; weighing 706g of concentrated hydrochloric acid with a mass concentration of 38%, diluting it to 1000ml with water, and stirring to obtain a dilute hydrochloric acid solution;
[0046] (2) 660 ml of the prepared zirconium-containing precursor solution, silicon-containing precursor solution and dilute acid solution were taken and placed in three 1000 ml dropping bottles with constant flow peristaltic pumps respectively; 660 ml of the prepared aluminum-containing precursor solution was taken and placed in a reactor with a jet flow agitator and a temperature control jacket; the temperature of the sodium aluminate solution was heated to 80°C by the temperature control medium in the temperature control jacket; the stirring speed was set to 1800 rpm; the flow rate of each peristaltic pump was 1 ml / s; the constant flow peristaltic pump and the jet flow agitator were turned on at the same time; the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution were pumped into the reactor at the same flow rate and flow rate in parallel; and the cooling The thermal integrated machine always controls the temperature of the reaction liquid in the reactor to 80°C. After the addition of liquid is completed, the peristaltic pump is turned off, and the stirring speed is continued at 1800rpm / min for 5 minutes to obtain an aluminum-based sol; after the obtained aluminum-based sol is allowed to stand in the reactor overnight, a dilute hydrochloric acid solution is added dropwise to adjust the pH value of the system to 5 to obtain an aluminum-based gel; the obtained aluminum-based gel is transferred to a Buchner funnel and repeatedly washed by suction filtration. When the PNa value of the filtrate is ≥2, the muddy wet gel after suction filtration is transferred to an oven and dried at 110°C for 8 hours to obtain a block dry gel, and the block dry gel is crushed into a powder with an average particle size of 5μm by a jet mill;
[0047] (3) The water-powder ratio is controlled to be 0.53, and diluted nitric acid with a mass concentration of 4% is used as a binder, and sesbania powder is used as a molding aid. The amount of sesbania powder added is 1% of the mass of the powder. The prepared aluminum-based powder is kneaded into a plastic material dough in a kneader; the material dough is transferred to an extruder, and extruded into a mold for preparing elliptical cylindrical extrusions. The outer diameter of the elliptical cylindrical extrusion obtained in this embodiment is 1 mm in the long axis direction, and the outer diameter of the short axis direction is 0.5 mm; the obtained extrusion is dried and processed into elliptical cylindrical particles with a length of 1 mm in a granulator, and then placed in a high-temperature furnace for roasting, the heating rate is 3°C / min, the constant temperature is 1100°C, the constant temperature time is 6 hours, and after natural cooling, zirconium and silicon modified aluminum-based composite catalyst carrier particles are obtained, which are recorded as sample 2.
[0048] The specific surface area and pore volume of the obtained samples were measured by N2 adsorption method on ASAP 2420 specific surface and voidage analyzer manufactured by Micromeritic Corporation, and the crushing strength of the obtained samples was measured by DLⅡ particle strength tester manufactured by Dalian Penghui Technology Development Co., Ltd. The test results are shown in Table 1.
[0049] Example 3
[0050] (1) Weigh 603 g of sodium aluminate (NaAlO 2 ) was dissolved in 800 ml of water, and the solution was poured into a 1000 ml volumetric flask and fixed to the standard scale to prepare an aluminum-containing precursor solution; 86 g of zirconium sulfate [Zr(SO 4 ) 2)] and 84g of thioglycolic acid were placed in a 1000ml volumetric flask, and an appropriate amount of water was added to dissolve the two, and then water was added to make the volume 1000ml to prepare a zirconium-containing precursor solution; 76g of sodium silicate (Na 2 SiO 3 ) add 500 ml of water to prepare a sodium silicate aqueous solution, add 150 g of acetylacetone to 300 ml of ethanol to prepare an acetylacetone alcohol solution, mix the two and pour them into a 1000 ml volumetric flask and add water to make the volume to 1000 ml, shake well to obtain a silicon-containing precursor solution; weigh 480 g of a concentrated sulfuric acid solution with a mass concentration of 75%, add water to dilute to 1000 ml to obtain a dilute sulfuric acid solution;
[0051] (2) 660 ml of the prepared zirconium-containing precursor solution, silicon-containing precursor solution and dilute acid solution were taken and placed in three 1000 ml dropping bottles with constant flow peristaltic pumps respectively; 660 ml of the prepared aluminum-containing precursor solution was taken and placed in a reactor with a jet flow agitator and a temperature control jacket; first, the sodium aluminate solution was heated to 100° C. by the heat transfer oil in the jacket, and the stirring speed was set to 3600 rpm. The flow rate of each peristaltic pump was 5 ml / s; then, the constant flow peristaltic pump and the jet flow agitator were turned on at the same time, and the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution were pumped into the reactor at the same flow rate and flow rate in a parallel flow manner. During the reaction process, , the temperature of the reaction liquid in the reactor is always controlled at 100°C by a hot and cold integrated machine, the peristaltic pump is turned off after the addition of liquid is completed, and the stirring is continued at a speed of 3600 rpm / min for 10 minutes to obtain an aluminum-based sol; after the obtained aluminum-based sol is allowed to stand in the reactor overnight, a dilute nitric acid solution is added dropwise to adjust the pH value of the system to 9 to obtain an aluminum-based gel; the obtained aluminum-based gel is transferred to a Buchner funnel and repeatedly washed by suction filtration. When the PNa value of the filtrate is ≥2, the muddy wet gel after suction filtration is transferred to an oven and dried at 100°C for 15 hours to obtain a block dry gel, and the block dry gel is crushed into a powder with an average particle size of 20 μm by a jet mill;
[0052] (3) The water-powder ratio is controlled to be 0.58, and diluted nitric acid with a mass concentration of 2% is used as a binder, and field sesbania powder is used as a molding aid. The amount of field sesbania powder added is 3% of the mass of the powder. The prepared aluminum-based powder is kneaded into a plastic dough in a kneader; the dough is transferred to an extruder, and extruded into strips through a mold for preparing multi-petal extrusions. The multi-petal extrusions prepared in this embodiment have an circumscribed circle diameter of 5 mm, a core diameter of 1.5 mm, and a plum blossom shape; the obtained extrusions are dried and prepared into multi-petal particles with an average length of 4 mm in a granulator, and then placed in a high-temperature furnace for roasting. The heating rate is 5°C / min, the constant temperature is 1300°C, and the constant temperature time is 3 hours. After natural cooling, zirconium and silicon modified aluminum-based composite catalyst carrier particles are obtained, which are recorded as sample 3.
[0053] The surface area and voidage analyzer ASAP 2420 manufactured by Micromeritics was used to analyze the 2 The specific surface area and pore volume of the obtained samples were measured by adsorption method, and the crushing strength of the obtained samples was measured by DLⅡ particle strength tester manufactured by Dalian Penghui Technology Development Co., Ltd. The test results are shown in Table 1.
[0054] Example 4
[0055] (1) Weigh 603 g of sodium aluminate (NaAlO 2 ) was dissolved in 800 ml of water, and the solution was poured into a 1000 ml volumetric flask and fixed to the standard scale to prepare an aluminum-containing precursor solution; 50 g of zirconium oxysulfate (ZrOSO 4 ) was dissolved in 500 ml of water, and 154 g of sodium dithiopropanesulfonate (C 3 H 7 O 3 S 3 Na), stir and dissolve, transfer the solution to a 1000 ml volumetric flask and dilute to standard scale with water to prepare a zirconium-containing precursor solution; weigh 61 g of sodium silicate (Na 2 SiO 3 ) was dissolved in 500 ml of water, and 149 g of triethanolamine (C 6 H 15 NO 3 ), after stirring and dissolving, transfer the solution to a 1000ml volumetric flask and dilute to the standard mark with water to obtain a silicon-containing precursor solution; weigh 681g of concentrated nitric acid with a mass concentration of 68% and place it in a 1000ml volumetric flask, add water and shake well, and dilute to the standard mark to obtain a dilute nitric acid solution;
[0056] (2) 660 ml of the prepared zirconium-containing precursor solution, silicon-containing precursor solution and dilute acid solution were taken and placed in three 1000 ml dropping bottles with constant flow peristaltic pumps respectively; 660 ml of the prepared aluminum-containing precursor solution was taken and placed in a reactor with a jet flow agitator and a temperature control jacket; the temperature of the sodium aluminate solution was heated to 95° C. by the temperature control medium in the temperature control jacket; the stirring speed was set to 2600 rpm / min; the flow rate of each peristaltic pump was 3 ml / s; the constant flow peristaltic pump and the jet flow agitator were turned on at the same time; the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution were pumped into the reactor at the same flow rate and flow rate in a parallel flow manner; The hot and cold integrated machine always controls the temperature of the reaction liquid in the reactor to 95°C. After the addition of liquid is completed, the peristaltic pump is turned off, and the stirring speed is continued at 2600rpm / min for 10 minutes to obtain an aluminum-based sol; after the obtained aluminum-based sol is allowed to stand in the reactor overnight, a dilute nitric acid solution is added dropwise to adjust the pH value of the system to 8.4 to obtain an aluminum-based gel; the obtained aluminum-based gel is transferred to a Buchner funnel and repeatedly washed by suction filtration. When the PNa value of the filtrate is ≥3, the muddy wet gel after suction filtration is transferred to an oven and dried at 110°C for 15 hours to obtain a block dry gel, and the block dry gel is crushed into a powder with an average particle size of 8μm by a jet mill;
[0057] (3) The water-powder ratio is controlled to be 0.53, and diluted nitric acid with a mass concentration of 4% is used as a binder, and sesbania powder is used as a molding aid. The amount of sesbania powder added is 2% of the mass of the powder. The prepared aluminum-based powder is kneaded into a plastic dough in a kneader; the dough is transferred to an extruder, and extruded into a cylindrical extrudate through a mold for preparing cylindrical extrudates. The diameter of the cylindrical extrudates prepared in this embodiment is 2 mm; the obtained extrudates are dried and prepared into cylindrical particles with an average length of 4 mm in a granulator, and then placed in a high-temperature furnace for calcination at a heating rate of 1.5°C / min, a constant temperature of 1250°C, a constant temperature time of 4 hours, and after natural cooling, zirconium and silicon modified aluminum-based composite catalyst carrier particles are obtained, which are recorded as sample 4.
[0058] The surface area and voidage analyzer ASAP 2420 manufactured by Micromeritics was used to analyze the 2 The specific surface area and pore volume of the obtained samples were measured by adsorption method, and the crushing strength of the obtained samples was measured by DLⅡ particle strength tester manufactured by Dalian Penghui Technology Development Co., Ltd. The test results are shown in Table 1.
[0059] Example 5
[0060] (1) Weigh 603 g of sodium aluminate (NaAlO 2 ) was dissolved in 800 ml of water, and the solution was poured into a 1000 ml volumetric flask and fixed to the standard scale to prepare an aluminum-containing precursor solution; 6 g of zirconium isopropoxide [ZrC 15 H 36 O 5] and 13g 8-hydroxyquinoline, dissolve them in an appropriate amount of anhydrous ethanol, transfer them to a 1000ml volumetric flask and dilute to 1000ml with anhydrous ethanol to prepare a zirconium-containing precursor solution; 76g sodium silicate (Na 2 SiO 3 ) add 300 ml of water to prepare a sodium silicate aqueous solution, add 243 g of sulfosalicylic acid to 500 ml of water to prepare a sulfosalicylic acid solution, mix the two and transfer to a 1000 ml volumetric flask and add water to make the volume to 1000 ml, shake well to obtain a silicon-containing precursor solution; weigh 682 g of concentrated nitric acid with a mass concentration of 68% and place it in a 1000 ml volumetric flask, add water and shake well to dilute to the standard scale line to obtain a dilute nitric acid solution;
[0061] (2) 660 ml of the prepared zirconium-containing precursor solution, silicon-containing precursor solution and dilute acid solution were taken and placed in three 1000 ml dropping bottles with constant flow peristaltic pumps respectively; 660 ml of the prepared aluminum-containing precursor solution was taken and placed in a reactor with a jet flow agitator and a temperature control jacket; first, the sodium aluminate solution was heated to 100° C. by the heat transfer oil in the jacket, and the stirring speed was set to 2500 rpm. The flow rate of each peristaltic pump was 3 ml / s; then, the constant flow peristaltic pump and the jet flow agitator were turned on at the same time, and the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution were pumped into the reactor at the same flow rate and flow rate in a parallel flow manner. During the reaction process, The temperature of the reaction liquid in the reactor was always controlled at 100°C by a hot and cold integrated machine, and the peristaltic pump was turned off after the addition of liquid was completed, and the stirring was continued at a speed of 2500 rpm / min for 8 minutes to obtain an aluminum-based sol; after the obtained aluminum-based sol was allowed to stand in the reactor overnight, a dilute nitric acid solution was added dropwise to adjust the pH value of the system to 8.3 to obtain an aluminum-based gel; the obtained aluminum-based gel was transferred to a Buchner funnel, and washed repeatedly by suction filtration, and when the PNa value of the filtrate was ≥2, the muddy wet gel after suction filtration was transferred to an oven and dried at 100°C for 15 hours to obtain a block dry gel, and the block dry gel was crushed into a powder with an average particle size of 15 μm by a jet mill;
[0062] (3) The water-powder ratio is controlled to be 0.58, and diluted nitric acid with a mass concentration of 2% is used as a binder, and sesbania powder is used as a molding aid. The amount of sesbania powder added is 3% of the mass of the powder. The prepared aluminum-based powder is kneaded into a plastic dough in a kneader; the dough is transferred to an extruder, and extruded into strips through a mold for preparing multi-petal extrusions. The multi-petal extrusions prepared in this embodiment have an circumscribed circle diameter of 5 mm, a core diameter of 1.5 mm, and a plum blossom shape; the obtained extrusions are dried and prepared into multi-petal particles with an average length of 4 mm in a granulator, and then placed in a high-temperature furnace for calcination at a heating rate of 5°C / min, a constant temperature of 1300°C, and a constant temperature time of 3 hours. After natural cooling, zirconium and silicon-modified aluminum-based composite catalyst carrier particles are obtained, which are recorded as sample 5.
[0063] The surface area and voidage analyzer ASAP 2420 manufactured by Micromeritics was used to analyze the 2 The specific surface area and pore volume of the obtained samples were measured by adsorption method, and the crushing strength of the obtained samples was measured by DLⅡ particle strength tester manufactured by Dalian Penghui Technology Development Co., Ltd. The test results are shown in Table 1.
[0064] Example 6
[0065] (1) Weigh 603 g of sodium aluminate (NaAlO 2 ) was dissolved in 800 ml of water, the solution was poured into a 1000 ml volumetric flask and the volume was fixed to the standard scale line to prepare an aluminum-containing precursor solution; 79 g of zirconium oxychloride (ZrOCl 2 8H 2 O) was dissolved in 500 ml of water, 94 g of citric acid was added, and after stirring and dissolving, the solution was transferred to a 1000 ml volumetric flask and diluted to the standard scale with water to prepare a zirconium-containing precursor solution; 4 g of sodium silicate (Na 2 SiO 3 ) was dissolved in 500 ml of water and 5 g of ammonium fluoride (FH 4 N), after stirring and dissolving, transfer the solution to a 1000ml volumetric flask and dilute to the standard mark with water to obtain a silicon-containing precursor solution; weigh 682g of concentrated nitric acid with a mass concentration of 68% and place it in a 1000ml volumetric flask, add water and shake well, and dilute to the standard mark to obtain a dilute nitric acid solution;
[0066] (2) 660 ml of the prepared zirconium-containing precursor solution, silicon-containing precursor solution and dilute acid solution were taken and placed in three 1000 ml dropping bottles with constant flow peristaltic pumps respectively; 660 ml of the prepared aluminum-containing precursor solution was taken and placed in a reactor with a jet flow agitator and a temperature control jacket; the sodium aluminate solution was heated to 90°C by the temperature control medium in the temperature control jacket; the stirring speed was set to 1800 rpm; the flow rate of each peristaltic pump was 3 ml / s; the constant flow peristaltic pump and the jet flow agitator were turned on at the same time; the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution were pumped into the reactor at the same flow rate and flow rate in parallel; and the mixture was stirred at room temperature by hot and cold water. The all-in-one machine always controls the temperature of the reaction liquid in the reactor to 90°C. After the addition of liquid is completed, the peristaltic pump is turned off, and the stirring speed is continued at 1800 rpm / min for 15 minutes to obtain an aluminum-based sol; after the obtained aluminum-based sol is allowed to stand in the reactor overnight, a dilute nitric acid solution is added dropwise to adjust the pH value of the system to 8 to obtain an aluminum-based gel; the obtained aluminum-based gel is transferred to a Buchner funnel, and repeatedly washed by suction filtration. When the PNa value of the filtrate is ≥3, the muddy wet gel after suction filtration is transferred to an oven and dried at 120°C for 15 hours to obtain a block dry gel, and the block dry gel is crushed into a powder with an average particle size of 10 μm by a jet mill;
[0067] (3) The water-powder ratio is controlled at 0.53, and diluted nitric acid with a mass concentration of 4% is used as a binder, and sesbania powder is used as a molding aid. The amount of sesbania powder added is 2% of the mass of the powder. The prepared aluminum-based powder is kneaded into a plastic dough in a kneader; the dough is transferred to an extruder, and extruded into a cylindrical extrudate through a mold for preparing cylindrical extrudates. The diameter of the cylindrical extrudates prepared in this embodiment is 2 mm; the obtained extrudates are dried and prepared into cylindrical particles with an average length of 2 mm in a granulator, and then placed in a high-temperature furnace for calcination at a heating rate of 2°C / min, a constant temperature of 1200°C, and a constant temperature time of 4 hours. After natural cooling, zirconium and silicon-modified aluminum-based composite catalyst carrier particles are obtained, which are recorded as sample 6.
[0068] The surface area and voidage analyzer ASAP 2420 manufactured by Micromeritics was used to analyze the 2 The specific surface area and pore volume of the obtained samples were measured by adsorption method, and the crushing strength of the obtained samples was measured by DLⅡ particle strength tester manufactured by Dalian Penghui Technology Development Co., Ltd. The test results are shown in Table 1.
[0069] Comparative Example 1
[0070] Weigh 603g of sodium aluminate (NaAlO 2 ) was dissolved in 800 ml of water, the solution was poured into a 1000 ml volumetric flask and fixed to the standard scale to prepare an aluminum-containing precursor solution; 49 g of zirconium oxychloride (ZrOCl 2 ·8H2O) was dissolved in 500ml water, stirred and dissolved, and then the solution was transferred to a 1000ml volumetric flask and diluted to the standard scale with water to prepare a zirconium-containing precursor solution; 38g sodium silicate (Na 2 SiO 3 ) was dissolved in 500 ml of water, and after stirring to dissolve, the solution was transferred to a 1000 ml volumetric flask and diluted to the standard mark with water to prepare a silicon-containing precursor solution; 682 g of concentrated nitric acid with a mass concentration of 68% was weighed and placed in a 1000 ml volumetric flask, and water was added and shaken to dilute to the standard mark to prepare a dilute nitric acid solution;
[0071] (2) 660 ml of the prepared zirconium-containing precursor solution, silicon-containing precursor solution and dilute acid solution were taken and placed in three 1000 ml dropping bottles with constant flow peristaltic pumps respectively; 660 ml of the prepared aluminum-containing precursor solution was taken and placed in a reactor with a jet flow agitator and a temperature control jacket; the temperature of the sodium aluminate solution was heated to 90° C. by the temperature control medium in the temperature control jacket; the stirring speed was set to 1800 rpm / min; the flow rate of each peristaltic pump was 3 ml / s; the constant flow peristaltic pump and the jet flow agitator were turned on at the same time; the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution were pumped into the reactor at the same flow rate and flow rate in a parallel flow manner; The hot and cold integrated machine always controls the temperature of the reaction liquid in the reactor to 90°C. After the addition of liquid is completed, the peristaltic pump is turned off, and the stirring speed is continued at 1800rpm / min for 15 minutes to obtain an aluminum-based sol; after the obtained aluminum-based sol is allowed to stand in the reactor overnight, a dilute nitric acid solution is added dropwise to adjust the pH value of the system to 8 to obtain an aluminum-based gel; the obtained aluminum-based gel is transferred to a Buchner funnel and repeatedly washed by suction filtration. When the PNa value of the filtrate is ≥3, the muddy wet gel after suction filtration is transferred to an oven and dried at 120°C for 15 hours to obtain a block dry gel, and the block dry gel is crushed into a powder with an average particle size of 10μm by a jet mill;
[0072] (3) The water-powder ratio is controlled to be 0.53, and diluted nitric acid with a mass concentration of 4% is used as a binder, and sesbania powder is used as a molding aid. The amount of sesbania powder added is 2% of the mass of the powder. The prepared aluminum-based powder is kneaded into a plastic dough in a kneader; the dough is transferred to an extruder, and extruded into a cylindrical extrudate through a mold for preparing cylindrical extrudates. The diameter of the cylindrical extrudates prepared in this embodiment is 2 mm; the obtained extrudates are dried and prepared into cylindrical particles with an average length of 2 mm in a granulator, and then placed in a high-temperature furnace for calcination at a heating rate of 2°C / min, a constant temperature of 1200°C, a constant temperature time of 4 hours, and after natural cooling, zirconium and silicon modified aluminum-based composite catalyst carrier particles are obtained, which are recorded as comparative sample 1.
[0073] The surface area and voidage analyzer ASAP 2420 manufactured by Micromeritics was used to analyze the 2 The specific surface area and pore volume of the obtained samples were measured by adsorption method, and the crushing strength of the obtained samples was measured by DLⅡ particle strength tester manufactured by Dalian Penghui Technology Development Co., Ltd. The test results are shown in Table 1.
[0074] Comparative Example 2
[0075] (1) Weigh 603 g of sodium aluminate (NaAlO 2 ) was dissolved in 800 ml of water, and the solution was poured into a 1000 ml volumetric flask and diluted to the standard scale to obtain an aluminum-containing precursor solution; 682 g of concentrated nitric acid with a mass concentration of 68% was weighed and placed in a 1000 ml volumetric flask, and water was added and shaken to dilute to the standard scale to obtain a dilute nitric acid solution;
[0076] (2) 660 ml of the prepared dilute acid solution was placed in a 1000 ml dropping bottle with a constant flow peristaltic pump, and 660 ml of the prepared aluminum-containing precursor solution was placed in a reactor with a Jet Flow agitator and a temperature control jacket. The temperature of the sodium aluminate solution was heated to 90° C. by the temperature control medium in the temperature control jacket, and the stirring speed was set to 1800 rpm / min. The flow rate of each peristaltic pump was 3 ml / s. At the same time, the constant flow peristaltic pump and the Jet Flow agitator were turned on to pump the dilute acid solution into the reactor. The temperature of the reaction liquid in the reactor was always controlled at 90° C. by the hot and cold integrated machine. ℃, after the addition of liquid is completed, the peristaltic pump is turned off, and the stirring speed is maintained at 1800rpm / min for 15 minutes to obtain an aluminum-based sol; after the obtained aluminum-based sol is allowed to stand in the reactor overnight, a dilute nitric acid solution is added dropwise to adjust the pH value of the system to 8 to obtain an aluminum-based gel; the obtained aluminum-based gel is transferred to a Buchner funnel and repeatedly washed by suction filtration. When the PNa value of the filtrate is ≥3, the muddy wet gel after suction filtration is transferred to an oven at 120℃ for drying for 15 hours to obtain a block dry gel, and the block dry gel is crushed into a powder with an average particle size of 10μm by a jet mill;
[0077] (3) The water-powder ratio is controlled to be 0.53, and diluted nitric acid with a mass concentration of 4% is used as a binder, and sesbania powder is used as a molding aid. The amount of sesbania powder added is 2% of the mass of the powder. The prepared aluminum-based powder is kneaded into a plastic dough in a kneader; the dough is transferred to an extruder, and extruded into a cylindrical extrudate through a mold for preparing cylindrical extrudates. The diameter of the cylindrical extrudates prepared in this embodiment is 2 mm; the obtained extrudates are dried and prepared into cylindrical particles with an average length of 2 mm in a granulator, and then placed in a high-temperature furnace for calcination. The heating rate is 2°C / min, the constant temperature is 1200°C, the constant temperature time is 4 hours, and the alumina carrier particles are obtained after natural cooling, which is recorded as comparative sample 2.
[0078] The surface area and voidage analyzer ASAP 2420 manufactured by Micromeritics was used to analyze the 2 The specific surface area and pore volume of the obtained samples were measured by adsorption method, and the crushing strength of the obtained samples was measured by DLⅡ particle strength tester manufactured by Dalian Penghui Technology Development Co., Ltd. The test results are shown in Table 1.
[0079] Table 1 Strength and specific surface area of samples obtained in various embodiments and comparative examples
[0080]
[0081]
[0082] Example 7
[0083] Using samples 1 to 6 and comparative samples 1 to 2 as carriers, Ir catalysts were prepared respectively by the equal volume impregnation method. The Ir loading was 18%, the reduction temperature was 450°C, the reducing gas was hydrogen, the reduction time was 5 hours, and the catalyst samples were obtained after natural cooling, recorded as catalyst samples 1 to 6 and catalyst ratio samples 1 to 2.
[0084] Using anhydrous hydrazine as the propellant, the thermal test performance of the hydrazine decomposition reaction of the catalyst sample and the catalyst comparison sample was tested on a 5N thruster. The results are shown in Table 2.
[0085] Using ADN as the propellant, the green propellant decomposition reaction thermal test performance of the catalyst sample and the catalyst comparison sample was tested on a 0.5N thruster. The results are shown in Table 3.
[0086] Table 2 Hydrazine decomposition reaction performance
[0087] Catalyst name Cold Start Times Number of pulses Crushing rate Hydrazine Catalyst sample 1 10000 times 1 million 1.5% 30kg / g Catalyst sample 2 9300 times 905,000 2.0% 30kg / g Catalyst sample 3 8500 times 803,000 2.7% 30kg / g Catalyst sample 4 7500 times 800,000 2.1% 30kg / g Catalyst sample 5 6300 times 788,000 3.1% 30kg / g Catalyst sample 6 7900 times 868,000 3.6% 30kg / g Catalyst comparison sample 1 3000 times 100,000 12.5% 15kg / g Catalyst comparison sample 1 500 times 10,000 18.2% 10kg / g
[0088] Table 3 Thermal test performance of ADN propellant
[0089]
[0090]
[0091] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A monoatomic dispersed zirconium-silicon modified alumina carrier, characterized in that: The carrier is composed of zirconium oxide, silicon oxide and aluminum oxide; by weight, the zirconium oxide content is 0.5-10%, the silicon oxide content is 0.5-8%, and the balance is aluminum oxide; the zirconium element and the silicon element are distributed on the surface and bulk of the aluminum oxide grains in an isolated single atomic state; The preparation method of the carrier comprises the following steps: (1) Preparing a precursor solution: dissolving sodium aluminate in water to prepare an aluminum-containing precursor solution, dissolving a soluble zirconium salt in water, adding a complexing agent I, preparing a zirconium-containing precursor solution, dissolving sodium silicate in water, adding a complexing agent II, preparing a silicon-containing precursor solution; (2) preparing aluminum-based composite powder: taking the same volume of aluminum-, zirconium-, silicon-containing precursor solution and dilute acid solution obtained in step (1), adding the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution to the aluminum-containing precursor solution at the same flow rate, controlling the stirring speed to 1800-3600 rpm, and the reaction temperature to 80-100° C. to obtain aluminum-based sol, and after standing for 10-24 hours, adjusting the pH value of the system to 5-9 with a dilute acid solution to obtain aluminum-based gel, and then washing, filtering, drying, and crushing to obtain aluminum-based composite powder; (3) Powder molding: The aluminum-based composite powder obtained in step (2) is mixed with a binder and a molding aid, kneaded, molded, granulated, and then calcined to obtain a catalyst carrier material with a macroscopic shape; The complexing agent I is one or more of 1,10-o-phenanthroline, disodium ethylenediaminetetraacetate, thioglycolic acid, mercaptoethylamine, sodium dimercaptopropanesulfonate, thiourea, 8-hydroxyquinoline, potassium cyanide, citric acid, tartaric acid, oxalic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid, ethylenediaminetetrapropionic acid, and triethylenetetramine; The complexing agent II is one or more of catechol, ammonium fluoride, acetylacetone, triethanolamine and sulfosalicylic acid.
2. The monoatomic dispersed zirconium-silicon modified alumina carrier according to claim 1, characterized in that: The specific surface area of the carrier is ≥180m 2 / g, pore volume ≥ 0.25cm 3 / g, strength 36~70Mpa.
3. A method for preparing the monoatomic dispersed zirconium-silicon modified alumina carrier according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: (1) Preparing a precursor solution: dissolving sodium aluminate in water to prepare an aluminum-containing precursor solution, dissolving a soluble zirconium salt in water, adding a complexing agent I, preparing a zirconium-containing precursor solution, dissolving sodium silicate in water, adding a complexing agent II, preparing a silicon-containing precursor solution; (2) preparing aluminum-based composite powder: taking the same volume of aluminum-, zirconium-, silicon-containing precursor solution and dilute acid solution obtained in step (1), adding the zirconium-containing precursor solution, the silicon-containing precursor solution and the dilute acid solution to the aluminum-containing precursor solution at the same flow rate, controlling the stirring speed to 1800-3600 rpm, and the reaction temperature to 80-100° C. to obtain aluminum-based sol, and after standing for 10-24 hours, adjusting the pH value of the system to 5-9 with a dilute acid solution to obtain aluminum-based gel, and then washing, filtering, drying, and crushing to obtain aluminum-based composite powder; (3) Powder molding: The aluminum-based composite powder obtained in step (2) is mixed with a binder and a molding aid, kneaded, molded, granulated, and then calcined to obtain a catalyst carrier material with a macroscopic shape; The complexing agent I is one or more of 1,10-o-phenanthroline, disodium ethylenediaminetetraacetate, thioglycolic acid, mercaptoethylamine, sodium dimercaptopropanesulfonate, thiourea, 8-hydroxyquinoline, potassium cyanide, citric acid, tartaric acid, oxalic acid, ethylene glycol bis(2-aminoethyl ether)tetraacetic acid, ethylenediaminetetrapropionic acid, and triethylenetetramine; The complexing agent II is one or more of catechol, ammonium fluoride, acetylacetone, triethanolamine and sulfosalicylic acid.
4. The preparation method according to claim 3, characterized in that: In step (1), the soluble zirconium salt is one or more of zirconium tetrachloride, zirconium oxychloride, zirconium sulfate, zirconium oxysulfate, and zirconium isopropoxide; The dilute acid solution is any one of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid and acetic acid, and the equivalent concentration of the dilute acid solution is 2-5 mol / L.
5. The preparation method according to claim 3, characterized in that: In step (2), the parallel flow rate is 1 to 5 ml / s; In the same volume of the zirconium-containing precursor solution, the silicon-containing precursor solution, the dilute acid solution, and the aluminum-containing precursor solution, the molar ratio of zirconium, silicon, hydrogen ions, and aluminum is (2-33): (4-85): 1000: 1000; The drying temperature is 100-120° C., and the drying time is 6-15 hours.
6. The preparation method according to claim 3, characterized in that: In step (3), the calcination temperature is 1100-1300° C.; The mass ratio of the aluminum-based composite powder, the binder and the molding aid is 100:(53-58):(1-3).
7. The preparation method according to claim 3, characterized in that: In step (3), the macroscopic catalyst carrier material is a particle with a circular, elliptical or multi-petal cross section and a screening diameter of 0.5 to 5 mm.
8. The preparation method according to claim 7, characterized in that: In step (3), the screening diameter is 0.8 to 2.0 mm.
9. Use of the monoatomic dispersed zirconium-silicon modified alumina carrier according to any one of claims 1 to 2 or the monoatomic dispersed zirconium-silicon modified alumina carrier prepared by the preparation method according to any one of claims 3 to 8 in the hydrazine decomposition reaction and ammonium dinitramide decomposition reaction of a monocomponent thruster.
Citation Information
Patent Citations
Method for preparing petroleum wax hydrofining catalyst
CN102039148A
Preparation method of high-temperature-resistant alumina with large specific surface area
CN102491389A
Preparation method of high-heat stable rare-earth modified alumina
CN102701246A
Preparation method of high temperature-resistant alumina aerogel material
CN103342537A
Preparation method of lanthanum modified aluminum oxide
CN109772289A